Microstructure and mechanical properties of Al-Mg-Si alloy fabricated by a short process based on sub-rapid solidification. (15th March 2020) - Liu, Ze-Tian; Wang, Bing-Yu; Wang, Cheng; Zha, Min; Liu, Guo-Jun; Yang, Zhi-Zheng; Wang, Jin-Guo; Li, Jie-Hua; Wang, Hui-Yuan
Abstract: Al-Mg-Si (AA6xxx) series alloys have been used widely in automotive industry for lightweight purpose. This work focuses on developing a short process for manufacturing Al-0.5Mg-1.3Si (wt.%) alloy sheets with good mechanical properties. Hereinto, a preparation route without homogenization was proposed on the basis of sub-rapid solidification (SRS) technique. The sample under SRS has fine microstructure and higher average partition coefficients of solute atoms, leading to weaker microsegregation owing to the higher cooling rate (160 °C/s) than conventional solidification (CS, 30 °C/s). Besides, Mg atoms tend to be trapped in Al matrix under SRS, inducing suppression of Mg2 Si, and promoting generation of AlFeSi phase. After being solution heat treated (T4 state), samples following the SRS route have lower yield strength compared with that by CS route, indicating better formability in SRS sample. After undergoing pre-strain and artificial aging (T6 state), the SRS samples have comparable yield strength to CS samples, satisfying the service requirements. This work provides technological support to industrially manufacture high performance AA6xxx series alloys with competitive advantage by a novel, short and low-cost process, and open a door for the further development of twin-roll casting based on SRS technique in industries.